Cobra [videorecording (DVD)] - Stallone, Sylvester; Stallone, Sylvester; Nielsen, Brigitte, 1963-; Santoni, Reni; Gosling, Paula (Warner Bros., 2015)
'Cobra', a cop, goes after psychopathic serial killers while protecting a young woman.